2017
DOI: 10.1016/j.neuroimage.2017.01.054
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-specific electrophysiologic correlates of resting state fMRI networks

Abstract: Resting state functional MRI (R-fMRI) studies have shown that slow (< 0.1 Hz), intrinsic fluctuations of the blood oxygen level dependent (BOLD) signal are temporally correlated within hierarchically organized functional systems known as resting state networks (RSNs) (Doucet et al., 2011). Most broadly, this hierarchy exhibits a dichotomy between two opposed systems (Fox et al., 2005). One system engages with the environment and includes the visual, auditory, and sensorimotor (SMN) networks as well as the dors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
107
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(119 citation statements)
references
References 100 publications
10
107
0
Order By: Relevance
“…We focused here on network nodes where electrode coverage was available, often only within a few sites per subject (especially in depth electrode cases). Consistent with previous studies (He et al, 2008, Keller et al, 2013, Ramot et al, 2013, Foster et al, 2015, Hacker et al, 2017, Kucyi et al, 2018a, we found that the spatial topography of functional connectivity patterns remained similar across task, rest and sleep states and between iEEG and within-individual resting state fMRI. We also found that even when dPPC-PMC and dAIC-PMC anticorrelations were not found, inter-network correlations between these pairs were typically within the lowest percentiles compared with all other region pairs.…”
Section: Intrinsic Inter-network Anticorrelationsupporting
confidence: 91%
See 1 more Smart Citation
“…We focused here on network nodes where electrode coverage was available, often only within a few sites per subject (especially in depth electrode cases). Consistent with previous studies (He et al, 2008, Keller et al, 2013, Ramot et al, 2013, Foster et al, 2015, Hacker et al, 2017, Kucyi et al, 2018a, we found that the spatial topography of functional connectivity patterns remained similar across task, rest and sleep states and between iEEG and within-individual resting state fMRI. We also found that even when dPPC-PMC and dAIC-PMC anticorrelations were not found, inter-network correlations between these pairs were typically within the lowest percentiles compared with all other region pairs.…”
Section: Intrinsic Inter-network Anticorrelationsupporting
confidence: 91%
“…A handful of iEEG studies involving recordings from putative DMN and DAN nodes have shown task-evoked HFB responses that resemble the antagonistic inter-network patterns observed in fMRI (Ossandon et al, 2011, Ramot et al, 2012, Raccah et al, 2018. In addition, resting state iEEG has revealed correlates of the DMN and DAN (Foster et al, 2015, Hacker et al, 2017, Kucyi et al, 2018a and that a subset of region pairs with resting BOLD anticorrelations exhibit weaker, but significant anticorrelations of slow (0.1-1 Hz) HFB activity (Keller et al, 2013).…”
Section: Introductionmentioning
confidence: 93%
“…Beyond the signal-to-noise limitations in human concurrent EEG-fMRI, there is evidence that γ-and β-band connectivity may contain information complementary to fMRI-derived connectivity. A weaker relation to fMRI connectivity has been reported for β and low-γ compared to other bands in intracranial electrophysiological recordings in humans (38,58) and in animals (59,60). The weaker relationship for β-and low γ-bands likely reflects a general property of the electrophysiology-fMRI relationship.…”
Section: Methodological Considerations and Limitationsmentioning
confidence: 82%
“…Traditionally, parcellation of cortex has depended heavily on anatomical techniques that cannot be applied in live subjects: cyto-, myelo-, and chemoarchitectonic markers, anterograde and retrograde tracers, and electron microscopy (Amir et al, 1993; Gerbella et al, 2007; Levitt et al, 1993; Rockland and Lund, 1983). More recently, technical advances have enabled cortical parcellation based on fMRI BOLD responses (Power et al, 2011; Vincent et al, 2007), optical imaging, diffusion weighted imaging, and electrocorticography (ECoG) (Hacker et al, 2012; He et al, 2008) in living subjects. To our knowledge, however, our study is first to do so based on spiking activity in association cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this large-scale parcellation based on BOLD seems to reflect large-scale electrophysiological properties as well, since the BOLD response fluctuations are closely related to local field potentials and spiking activity within each voxel (Logothetis et al, 2001; Scholvinck et al, 2010). Moreover, the BOLD response correlations across voxels can be mapped to the correlation of the slow cortical potentials in the corresponding locations, as evidenced by electrocorticography (ECoG) (Hacker et al, 2012; He et al, 2008). …”
Section: Discussionmentioning
confidence: 99%